Synthesis and crystal structure of a new isomer of poly[di-μ3-cyanido-μ-2,6-dimethylpyrazine-dicopper(I)] - Christian Näther (Acta Crystallographica Section E: Crystallographic Communications)
The title compound, [Cu2(CN)2(C6H8N2)]n or Cu2(CN)2(2,6-dimethylpyrazine), was prepared by the reaction of copper(I) cyanide with 2,6-dimethylpyrazine in water. Its asymmetric unit consists of two crystallographically independent copper(I) cations and cyanide anions as well as one crystallographically independent 2,6-dimethylpyrazine ligand in general positions. Each copper cation is fourfold coordinated by one N atom of the 2,6-dimethylpyrazine ligand and three cyanide anions, that are disordered so that each C and N position has mixed occupancy with a ratio between N and C of 94:6 and 77:23. The copper cations are linked by the cyanide atoms into layers that are further connected into a 3D network by the 2,6-dimethylpyrazine ligands. Powder X-ray diffraction (PXRD) proves that a pure crystalline phase has been obtained. It is noted that this crystal structure represents a new isomer of Cu2(CN)2(2,6-dimethylpyrazine), which has already been reported in the literature [Chesnut et al. (2001). J. Chem. Soc. Dalton Trans. pp. 2567–2580].